Bridging Meaning and Tradition: A Transitivity Examination of Makassar Aruk Texts in Wedding Discourse - Nasrullah, Ince; Suryaningsih, Ita; Kasmawati, Kasmawati (ppjbsip, 2024)
This study delves into a comprehensive analysis of language structures within the aruk text. Employing a qualitative approach, the research focuses on a meticulous examination of the transitivity system. The findings reveal the existence of six distinct process types within each clause, intricately involving the relationships among participants and their respective circumstances. Notably, the study identifies consistent predicate patterns in the formation of aruk texts, particularly prevalent in the context of wedding expressions within the metafunction of the Makassar language. Furthermore, the research uncovers that the articulation of meaning, based on linguistic data, encompasses ideational, interpersonal, and textual dimensions. This multifaceted analysis enables a nuanced understanding of meaning, elucidating the metafunction of language through the exploration of words, phrases, and clauses pertaining to the speaker's conceptual domain.